A Scalable Two-Phase Bottom-Up Specialization Prospective For Data Anonymization Using Map Reduce On Cloud (International Journal of Engineering and Computer Science, 2017)
A scalable two-phase bottom-up specialization prospective to anonymize large-scale data sets using the Map Reduce framework on cloud, this is todays emerging trend and requirement.The people theydon’t want to share their sensitive information with unauthorized user, so they want to hide the informationfrom unauthorized person.Emerging techniques such as K-Anonymity, Map Reduceand Data Anonymization are used but there are lot of drawbacksalso occurring in existing method, like privacy, third party access and so on. So in this paperwe are going to see about how bottom up specialization for data anonymization using map reduce on cloud isused for preserving the privacy of user’s data’s.